ANALISIS ALTMAN Z”SCORE MODIFICATION DALAM MEMPREDIKSI FINANCIAL DISTRESS PERUSAHAAN PUBLIK SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESI (BEI) - Hariyanto, Hariyanto (LAND JOURNAL, 2024)
This study aims to predict financial distress of transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) using the Altman Z "Score Modification method. The data used is the company's financial statements for the 2019-2022 period. The sample for this study used purposive sampling in accordance with the company's criteria. The results of the study using the Altman Z "Score Modification method found that every year there are companies that are predicted to experience financial distress. In 2019 there were 6 companies that were predicted to experience financial distress, namely GIAA, ASSA, BTPR. TRJA, CMPP, and TAXI. In 2020, the 6 companies, namely GIAA, ASSA, BTPR, TRJA, CMPP, and TAXI, experienced financial distress again. In 2021 the number of companies experiencing financial distress is only 5 companies, namely GIAA, ASSA, BTPR, CMPP, and TAXI. However, in 2022 there were again 6 companies experiencing financial distress, namely ASSA, LRNA, BTPR, CMPP, TAXI, and Heli. Of the 9 companies, only 1 company has a healthy financial condition, namely PT Blue Bird Indonesia (BIRD), because for 4 years it has always been in the safe zone with a Z "score value above 2.6.